Seismic fragility and risk assessment of high-speed railway continuous-girder bridge under track constraint effect - Cui, Shengai; Guo, Chen; Su, Jiao; Cui, Enqi; Liu, Pin (Bulletin of earthquake engineering, 2019)
The prestressed-concrete continuous-girder bridge is one of the major high-speed railway bridges that plays an essential role in the railway. Using a typical high-speed railway continuous-girder bridge as a case study, a track-bridge longitudinal interaction model has been initially established with a comprehensive consideration of the components including rail, track slab, bed plate, rail fastener, cement asphalt mortar, sliding layer, and bridge structure. The damage states of the bridge and the seismic capacity model for key structural components of the bridge under various damages were defined. A probabilistic seismic demand model was constructed for structural components according to the incremental dynamic analysis of a suite of selected ground-motion. The fragility curves of the bridge components were derived and compared with that of the bridge model without a track system. Then, the failure probability of the bridge system was estimated using the first-order boundary method. Finally, the risk of the bridge was assessed via the numerical convolution method using both the fragility curves and seismic hazard function. The results are drawn as follows: (1) Owing to the longitudinal constraint of the track system, the dynamic characteristics of the bridge are changed; (2) A total of four damage levels occurred on the bridge pier without the track system, but only light and moderate damage levels appear due to the track constraint; (3) Under the same peak ground acceleration, the damage exceeding probability of the model without the track system is significantly greater than that with the track system; (4) Under the slight and moderate damage states, the upper and lower limits of the system fragility curves are governed by bridge pier. They are governed by the bearing with very low failure probability under the extensive and complete damage states; and (5) Within the 100-year design period, the probability that the bridge structure subject to slight and moderate damages is “occasional”, while it is “very unlikely” that the structure will suffer from the extensive and complete damages.